Vigilância do desenvolvimento na caderneta da criança : efeito de uma intervenção com enfermeiros - Dias, Tayanne Kiev Carvalho (2024)
Introduction: the child’s handbook, considered a passport of citizenship, is a roadmap for the continuity of child health care, aimed at the practice of Child Development Surveillance, and is crucial in the prevention of morbidity and mortality, as its records allow for the early identification of diseases. Objective: to analyze the effect of an educational intervention on the recording of Developmental Surveillance Actions in the Child’s Handbook with nurses from the Family Health Strategy in light of Ausubel's Theory. Methodological Pathway: quasi-experimental study, typified as before-and-after, with a quanti-qualitative approach, from the perspective of Ausubel’s Theory of Significant Learning, conducted between June and October 2022, with 45 nurses working in the Family Health Strategy of Health District III in the town of João Pessoa – Paraíba. A previously constructed and validated instrument was used to evaluate before and after the educational activity, in addition to a focus group, which was subjected to the thematic analysis technique. In the statistical analysis, a descriptive analysis was carried out, where the chi-squared test was calculated considering a significance level of p≤5%. The research project was approved by the Ethics Committee under nº 97362718.1.0000.5188. Results: the instrument used to evaluate knowledge and practice regarding actions to record developmental surveillance in the child’s handbook showed an increase in the percentage of correct answers given by nurses after training. Furthermore, there was a positive impact after the educational intervention on the acquisition of new knowledge and practices during the nurses’ childcare consultations, in addition to generating transformations in the nurses’ work process, valuing the child’s handbook by making them responsible for using it during child development surveillance. Conclusions: the educational intervention could bring about significant improvements in the knowledge and practice of nurses working in Primary Health Care in terms of monitoring the growth and development of children during childcare visits. It is believed that the implementation of training to strengthen the use of the handbook should be a priority in health practices, aiming not only to improve the quality of care, but also to strengthen the bond between health professionals and families, promoting more comprehensive and effective care for children, contributing to their full development.